Epistemological and conceptual considerations for the study of the body in dance - Escudero, María Carolina (Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación, 2011)
The reflections expressed in this paper were originated from my research to carry out my PhD thesis. They have a twofold interest, on the one hand, formalize some of problems that research on the body generates; to the other hand, explain some methodological considerations that allowed me solve them. With that purpose I will work with the Foucauldian categories of problematization, experience and hermeneutics. In relation to them is done a reading in epistemological and methodological function in order to show a process, of sharing a way of thinking, to constructing a thought. I want to show how we use the words we use and what kind of subjective movement involves thinking